Cutting-edge science creating solutions for African agriculture - International Livestock Research Institute (International Livestock Research Institute, 2012)
Research scientist, Appolinaire Djikeng, Technology Manager at the Biosciences eastern and central Africa-International Livestock Research Institute (BecA-ILRI) Hub at the International Livestock Research Institute (ILRI) speaks of his passion to see science help Africa better participate in the global scientific community and to see more science-driven decision-making in the continent. At the BecA-ILRI Hub, African scientists are using the latest tools and technologies to find solutions for Africa's most pressing agricultural problems.